2022
DOI: 10.1186/s12951-022-01654-9
|View full text |Cite
|
Sign up to set email alerts
|

AGuIX nanoparticles enhance ionizing radiation-induced ferroptosis on tumor cells by targeting the NRF2-GPX4 signaling pathway

Abstract: In the frame of radiotherapy treatment of cancer, radioresistance remains a major issue that still needs solutions to be overcome. To effectively improve the radiosensitivity of tumors and reduce the damage of radiation to neighboring normal tissues, radiosensitizers have been given increasing attention in recent years. As nanoparticles based on the metal element gadolinium, AGuIX nanoparticles have been shown to increase the radiosensitivity of cancers. Although it is a rare nanomaterial that has entered prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
0
23
1
Order By: Relevance
“…However, it must be pointed out that radiosensitizing effects on cells has been reported for the original AGuIX@ platform containing Gd [ 30 , 37 ]. The Gd concentration to obtain such radiosensitive impact on cancer cells was reported for nanoparticles concentrations from 100 µM up to 1 mM [ 38 ]. Herein, the concentration of lanthanide was at least four times lower than the minimal concentration reporting effective radiosensitization, respectively, 16 and 25 µM for Tb and Gd ( Figure 5 c).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be pointed out that radiosensitizing effects on cells has been reported for the original AGuIX@ platform containing Gd [ 30 , 37 ]. The Gd concentration to obtain such radiosensitive impact on cancer cells was reported for nanoparticles concentrations from 100 µM up to 1 mM [ 38 ]. Herein, the concentration of lanthanide was at least four times lower than the minimal concentration reporting effective radiosensitization, respectively, 16 and 25 µM for Tb and Gd ( Figure 5 c).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Growing evidence has revealed that the lipid and amino acid metabolic pathways are involved in the regulation of ferroptosis. 15,39 Ferroptosis is characterized by the accumulation of lipid hydroperoxides and ROS derived from iron metabolism. 40,41 It can be triggered in cancer cells by depleting GSH or inhibiting GPX4.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, BM can induce the release of activated Nrf2, resulting in Nrf2 protein stabilization and nuclear translocation. 39 Lip-1 is an effective inhibitor of ferroptosis. BM significantly altered the effects of curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…We have reason to believe further efforts will incorporate ICG-coated SPIO-nanoparticle clusters into cell-specific technologies and will contribute to the wider usage of photoacoustic imaging in surgery. [82] To our knowledge, materials with high atomic numbers, including silver, gold, [83] hafnium, [84] and gadolinium [85] have been well-explored NP-mediated deposition of radiation, but limited biocompatibility might hinder translation of these heavy-metalbased technologies in clinical. By comparison, magnetic nanoparticles like iron oxide nanoparticles have significant advantages of FDA approval, good biocompatibility, and superparamagnetic for magnetic resonance imaging.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%